Molecular detection and characterization of Hepatozoon canis in stray dogs from Cuba - Díaz-Sánchez, Adrian Alberto; Hofmann-Lehmann, Regina; Meli, Marina L.; Roblejo-Arias, Lisset; Fonseca-Rodríguez, Osvaldo; Castillo, Anisleidy Pérez; Cañizares, Ernesto Vega; Rivero, Evelyn Lobo; Chilton, Neil B.; Corona-González, Belkis (Parasitology international, 2021)
Canine hepatozoonosis caused by Hepatozoon canis is a worldwide distributed tick-borne disease of domestic and wild canids that is transmitted by ingestion of Rhipicephalus sanguineus sensu lato (s.l.) ticks. The present study was aimed to determine the prevalence of Hepatozoon infections in 80 stray dogs from Havana Province in Cuba, and to confirm the species identity and phylogenetic relationships of the causative agent. Samples were screened by microscopical examination of thin blood smears for the presence of Hepatozoon spp. gamonts and by genus-specific SYBR green-based real-time PCR assay targeting the 18S rRNA gene. Direct microscopy examination revealed Hepatozoon gamonts in the peripheral blood of 8 dogs (10.0%; 95% CI: 4.80–18.0%), while 38 animals (47.5%; 95% CI: 36.8–58.4%) were PCR-positive, including all microscopically positive dogs. Hence, the agreement between the two detection methods was ‘poor’ (κ = 0.20). Hematological parameters did not differ significantly between PCR-positive and PCR-negative dogs (p > 0.05). The DNA sequences of the 18S rRNA gene of the Hepatozoon spp. from Cuban dogs showed a nucleotide identity >99% with those of 18S rRNA sequences of Hepatozoon canis isolates from Czech Republic, Brazil and Spain. Phylogenetic analysis revealed that obtained sequences clustered within the Hepatozoon canis clade, different from the Hepatozoon felis or Hepatozoon americanum clades. The present study represents the first molecular characterization of Hepatozoon canis in stray dogs within Cuba. [Display omitted] •First report and molecular characterization of Hepatozoon canis in dogs (Canis lupus familiaris) from Cuban.•Evidence of microscopical examination and SYBR green qPCR assay suggested the presence of hemoparasite Hepatozoon spp.•DNA sequencing and phylogenetic analysis based on the 18S rRNA gene confirm the Hepatozoon canis infection in dogs.•Hematological parameters did not differ significantly between PCR-positive and PCR-negative dogs (p>0.05).•The decreased values of hematocrit (HCT) and total platelet counts (PLT) suggested the occurrence of coinfections.